Structure of an epiphytic hydroid community on Cystoseira at two sites of different wave exposure - Faucci, Anuschka; Boero, Ferdinando (Scientia Marina, 2000)
Epiphytism is a strategy by which opportunistic species such as hydroids, escape the intense levels of competition in marine hard bottom communities. Species of the macroalgae Cystoseira have a seasonal turnover of the frond, and we hypothesise that epiphytic hydroids colonising such an unstable substrate might show some degree of specialisation. Here the first systematic study on hydroid-Cystoseira communities is presented. In particular, the seasonal and spatial distribution of epiphytic hydroids on three species of Cystoseira at two sites of different wave exposure at Porto Cesareo (Ionian Sea/Italy) were investigated. Thirty-two hydroid species were recorded which are well known from other substrates and thus are not specific to Cystoseira; dominant species were all thecates. The influence of biological factors such as competition and the structure and abundance of the host, seem to have little influence on the hydroid community. The factors of greatest influence were mostly abiotic: sedimentation rate, nutrient levels, temperature and most especially water movement. The importance of water movement was evident in the higher colonisation of algal stems, higher hydroid frequency, larger colonies, reduced colony height, species composition, and distribution on the stems at the wave-exposed site.